Penyuluhan Investasi Bodong: Meningkatkan Kewaspadaan Masyarakat terhadap Penipuan Berkedok Investasi Di Kecamatan Siulak Kabupaten Kerinci - Regen, Ronal; Bustami, Alek Wissalam; Wahyu, Wawan Devis; Novianto, Wawan; Busni, Darti (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
Fraudulent investments have become a significant problem in Indonesia, including in Siulak District, Kerinci Regency, where a high number of people fall victim to investment fraud. A lack of understanding of legitimate investments and low financial literacy have resulted in numerous victims, especially among university students, housewives, and the elderly. Therefore, outreach based on real-world case studies is crucial to enhance public vigilance against investment-themed fraud. This study employs a direct outreach method with an educational approach that includes introducing the definition of fraudulent investments, the characteristics of legal investments, and how to identify illegal ones. The findings indicate that the outreach activity successfully increased public understanding of the difference between legitimate and fraudulent investments and improved their vigilance towards suspicious investment offers. The discussion shows that case study-based outreach can effectively reduce the number of new victims of fraudulent investments and strengthen the community's role in protecting themselves and others from investment fraud.